2005
DOI: 10.1016/j.cell.2004.11.042
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Helicase Activity of the Ribosome

Abstract: Most mRNAs contain secondary structure, yet their codons must be in single-stranded form to be translated. Until now, no helicase activity has been identified which could account for the ability of ribosomes to translate through downstream mRNA secondary structure. Using an oligonucleotide displacement assay, together with a stepwise in vitro translation system made up of purified components, we show that ribosomes are able to disrupt downstream helices, including a perfect 27 base pair helix of predicted T(m)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
480
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 457 publications
(507 citation statements)
references
References 34 publications
24
480
2
1
Order By: Relevance
“…3a). The oligonucleotides did not affect translation as such, because the ribosome can efficiently dissolve duplexes of moderate stability 21 . However, bypassing was abolished (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a). The oligonucleotides did not affect translation as such, because the ribosome can efficiently dissolve duplexes of moderate stability 21 . However, bypassing was abolished (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reconstructions reveal that the pseudoknot interacts with the ribosome at the entrance to the mRNA channel, in close association with a likely mammalian 80S helicase (52). Superimposition of our pseudoknot-stalled and control map shows differences between the maps found at this entrance tunnel (25).…”
Section: Introductionmentioning
confidence: 81%
“…It has been shown that the ribosome itself acts a helicase comprised of ribosomal proteins S3, S4 and S5 which line the mRNA entrance tunnel in the case of prokaryotic ribosomes (25,52). Specific RNA structures, such as the BWYV pseudoknot, resist unwinding giving rise to increased tension in the spacer and subsequent disruption of the codon-anticodon interaction.…”
Section: The Beet Western Yellow Virus -1 Frameshift Signalmentioning
confidence: 99%
“…To release this tension, the pseudoknot could be unwound or the mRNA can shift by one nucleotide producing a Ϫ1 frameshift. An alternate model suggests that proteins S3, S4, and S5 of the ribosome function as an RNA helicase to unfold mRNA structures (18,19). A stable three-stranded structure such as a pseudoknot would provide a barrier for the helicase, inhibiting the unwinding of the pseudoknot and preventing forward motion of the elongating ribosome in the reference frame.…”
mentioning
confidence: 99%